2019
DOI: 10.1002/jcla.23072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ureaplasma urealyticum, Chlamydia trachomatis, and Neisseria gonorrhoeae in gynecological outpatients, Taizhou, China

Abstract: Objectives Ureaplasma urealyticum (UU), Chlamydia trachomatis (CT), and Neisseria gonorrhoeae (NG) are highly prevalent worldwide and may lead to some genital diseases. The objective of this large‐scale study was to estimate the prevalence characteristics of UU, CT, and NG among women in Taizhou, Zhejiang Province, China. Methods A total of 13 303 women who visited the gynecologic outpatient service of Taizhou First People's Hospital in Taizhou from 2013 to 2018 were analyzed. The testing of UU, CT, and NG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Compared with the CT prevalence in countries such as United States (7.4% in pregnant women during 2014–2017) [ 22 ] and low- and middle-income countries in Asia (0.8% in 2012–2015) [ 23 ], our study population had a higher prevalence: 6.7% for pregnant women, 8.2% for gynecology clinic attendees, and 5.9% for infertility clinic attendees. We also note a relatively high prevalence in women from Shenzhen (10.1% in sexual and reproductive health clinics in 2018) [ 24 ], Taizhou (10.2% in gynecology outpatients during 2013–2018), and Beijing (5.9% in outpatient clinic attendees during 2013–2016) [ 16 ]. The lower prevalence for women attending infertility clinics may be explained by the following reasons: (a) we included all subfertile women, and ~30% of them suffered tubal infertility; (b) we used NAAT to test chlamydia, which measures current infection status and not past infection; a study on CT and infertility showed that a past CT infection was a key determinant of tubal infertility [ 25 ]; and (c) past chlamydia infection has ascended to and been recurrent in uteran tubal, and other remote sites in infertile women, but it cannot be detected in urine or cervical swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the CT prevalence in countries such as United States (7.4% in pregnant women during 2014–2017) [ 22 ] and low- and middle-income countries in Asia (0.8% in 2012–2015) [ 23 ], our study population had a higher prevalence: 6.7% for pregnant women, 8.2% for gynecology clinic attendees, and 5.9% for infertility clinic attendees. We also note a relatively high prevalence in women from Shenzhen (10.1% in sexual and reproductive health clinics in 2018) [ 24 ], Taizhou (10.2% in gynecology outpatients during 2013–2018), and Beijing (5.9% in outpatient clinic attendees during 2013–2016) [ 16 ]. The lower prevalence for women attending infertility clinics may be explained by the following reasons: (a) we included all subfertile women, and ~30% of them suffered tubal infertility; (b) we used NAAT to test chlamydia, which measures current infection status and not past infection; a study on CT and infertility showed that a past CT infection was a key determinant of tubal infertility [ 25 ]; and (c) past chlamydia infection has ascended to and been recurrent in uteran tubal, and other remote sites in infertile women, but it cannot be detected in urine or cervical swabs.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a recent Chinese study, Ureaplasma urealyticum was found in 62% of patients and Chlamydia trachomatis in 10%, using real-time polymerase chain reaction. 6 However, lower rates of genital mycoplasma were noted in an Indian study by Arif et al Among 218 endocervical swabs, Ureaplasma spp., Mycoplasma hominis, Chlamydia trachomatis and Neisseria gonorrhoeae were found in 5.6%, 2.6%, 8% and 3%, respectively. 3 Notably, culture for N. gonorrhoea was negative in all patients.…”
Section: Discussionmentioning
confidence: 92%
“…found Ureaplasma and Chlamydia trachomatis coinfection in 7.3% of cases. 6 The coinfection of Chlamydia trachomatis with Ureaplasma has survival advantage as indicated in a few studies. 9…”
Section: Discussionmentioning
confidence: 99%
“… 1 It has been reported that the total infection rate of mycoplasma of 4082 patients with urogenital tract infection in China is 38.39%, mainly infected by single U. urealyticum , 2 which is inconsistent with some research results. 3 5 It suggests that there are some differences in the distribution of mycoplasma in different areas. It may be related to the different levels of antibiotic use, sampling sites, detection reagents, and laboratory precision in different regions.…”
Section: Introductionmentioning
confidence: 99%